Enhancing ammonium oxidizing bacteria activity was key to single-stage partial nitrification-anammox system treating low-strength sewage under intermittent aeration condition. (May 2017) - Miao, Yuanyuan; Zhang, Liang; Li, Baikun; Zhang, Qian; Wang, Simeng; Peng, Yongzhen
Graphical abstract: Highlights: AOB played a main role in SPN/A nitrogen performance. Anammox bacterial activity increased with AOB activity despite high NOB activity. Combining intermittent aeration and bio-augmentation enhanced SPN/A stabilization. Abstract: Intermittent aeration and bio-augmentation were integrated to enhance single-stage partial nitrification-anammox (SPN/A) stability over 235-day operational period treating low-strength sewage. The effect of bio-augmentation sludge (with different abundances of ammonium oxidizing bacteria (AOB) and nitrite oxidizing bacteria (NOB)) was determined. Partial nitrification sludge based bio-augmentation increased the total nitrogen (TN) removal efficiency from 29.1% to 70%, followed by the nitrification sludge (from 38.1% to 65.4%), then the denitrifying phosphorus sludge (from 42.1% to 54.4%). The evolution of bacteria activity and communities showed that anammox activity increased with the enhancement of AOB activity, and higher AOB abundance led to higher anammox bacterial abundance despite high NOB abundance. The enhancement of AOB activity produced more nitrite, anammox bacteria gained more nitrite than NOB since intermittent aeration selectively inhibited NOB, thus the reactor stability enhanced substantially. This study highlights the significance of enhancing AOB activity to ensure long-term operational stability of SPN/A processes.